Pengaruh Motivasi, Pelatihan dan Lingkungan Kerja Non Fisik Terhadap Kinerja Sales People pada Jaringan Dealer PT. Astra Honda Motor di Provinsi Nusa Tenggara Barat - Musyafa Rois; Tin Agustina; Yunus Handoko (Jurnal Syntax Admiration, 2023)
Indonesia's economic growth is supported by several sectors, one of which is the manufacturing sector. The manufacturing sector contributed 16.77 percent to national economic growth in the first quarter of 2023. According to the 2022 business competition index in Indonesia, Indonesia's score is 4.87 on a scale of 7, which has increased from previous years. The increase in the business competition index number illustrates the company's need to be able to optimize its resources and increase company productivity. In a company, employee performance greatly affects the quality of the products and services produced. With the need to increase company productivity, employee performance improvement is also needed so that companies are able to maintain business existence and encourage better company progress. Companies that are able to encourage the performance of their employees tend to have better quality products and services. Therefore, companies must encourage the performance of their employees in order to compete with changing market conditions from time to time. This study aims to determine the effect of motivation, training and non-physical work environment on the performance of sales people at the dealer network of PT. Astra Honda Motor in the province of West Nusa Tenggara (NTB). This research is a quantitative research with a sample of 90 sales people, the data collection method was carried out using an online questionnaire with a Google form. The analysis technique used in this study is multiple linear regression with hypothesis testing t-test and F-test. The results showed that motivation, training and the non-physical work environment had a partial and simultaneous positive effect on the performance of sales people at the dealer network of PT. Astra Honda Motor in the province of NTB.